2015
DOI: 10.1007/s10694-015-0520-z
|View full text |Cite
|
Sign up to set email alerts
|

Ignition of Wood Fencing Assemblies Exposed to Continuous Wind-Driven Firebrand Showers

Abstract: Post-fire studies conducted by NIST on the Waldo Canyon Fire in Colorado (2012) determined that wood fencing assemblies are believed to be vulnerable to ignition from firebrand showers in Wildland-Urban Interface fires, but again there has never been any experimental verification of this ignition mechanism. As a result, a series of experiments were conducted to examine ignition of wood fencing assemblies subjected to continuous, wind-driven firebrand showers. Western Red Cedar and Redwood fencing assemblies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
0
38
1
Order By: Relevance
“…Firebrands generated in this study were commensurate to those measured from burning structure components. For reference, the average projected area of firebrands generated in this study tailored to burning structure components was 1.56 cm 2 ± 0.85 cm 2 , as compared to 0.77 cm 2 ± 0.2 cm 2 , in prior studies of continuous firebrand generation tailored to burning trees and data from an actual WUI fire, where Douglas‐fir wood pieces were used to generate firebrands .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Firebrands generated in this study were commensurate to those measured from burning structure components. For reference, the average projected area of firebrands generated in this study tailored to burning structure components was 1.56 cm 2 ± 0.85 cm 2 , as compared to 0.77 cm 2 ± 0.2 cm 2 , in prior studies of continuous firebrand generation tailored to burning trees and data from an actual WUI fire, where Douglas‐fir wood pieces were used to generate firebrands .…”
Section: Resultsmentioning
confidence: 94%
“…The feeding rate was varied to determine the optimal conditions for continuous firebrand showers. Based on prior work, a wood mass loading 150 g to 200 g every 15 s resulted in adequate firebrand generation . As a result, in these experiments, 170 g ± 30 g, fed into the Dragon every 15 s provided an adequate firebrand generation rate to ignite building materials.…”
Section: Experimental Descriptionmentioning
confidence: 82%
See 2 more Smart Citations
“…Examples of attached building components include wood fencing assemblies. The authors demonstrated that full-scale fencing assemblies may be ignited by firebrand showers, but the capability of the ignited fencing to transfer the fire to an adjacent structure, such as wall assembly, was not considered [4]. …”
Section: Introductionmentioning
confidence: 99%